Overconsumption, credit rationing and bailout monetary policy: A Minskyan perspective - Matthieu Charpe; Peter Flaschel; Christian R. Proa\~no; Willi Semmler (Intervention. European Journal of Economics and Economic Policies, 2009)
We consider a Keynes-Goodwin model of effective demand and the distributive cycle where workers purchase goods and houses with a marginal propensity significantly larger than one. They therefore need credit, supplied from asset holders, and have to pay interest on their outstanding debt. In this initial situation, the steady state is attracting, while a marginal propensity closer to one makes it repelling. The stable excessive overconsumption case can easily turn from a stable boom to explosiveness and from there through induced processes of credit rationing into a devastating bust. In such a situation the central bank may prevent the worst by acting as creditor of last resort, purchasing loans where otherwise debt default (and bankruptcy regarding house ownership) would occur. This bail-out policy can stabilize the economy and also reduces the loss of homes of worker families.
Keywords: E24; E31; E32; 330; mortgage loans; booms; debt default; busts; creditor of last resort